DAMPAK KB TERHADAP KESEJAHTERAAN: MITOS DAN KENYATAAN* - Faturochman Faturochman; Wini Tamtiari; Henry Sembiring (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1998)
Family planning is an instrument to achieve family welfare but it is not the only one. However, the simplification of family planning-family welfare linkage has exagerated the family planning role. Many studies, such as conducted by Population Studies Center Gadjah Mada University, show that the direct effects of family planning practice and fertility on family welfare are weak. Understandingthat the role is not big as expected, BKKBN introduced family welfare program. The program seems meaningful but institutionally it looks inappropriate. We suggest BKKBN to concentrate on its core bussines,e.g. serving FP,rather to do the family welfare program.